iTRAQ-Based Proteomics Reveals Gu-Ben-Fang-Xiao Decoction Alleviates Airway Remodeling via Reducing Extracellular Matrix Deposition in a Murine Model of Chronic Remission Asthma - Xing, Qiongqiong; You, Yannan; Zhao, Xia; Ji, Jianjian; Yan, Hua; Dong, Yingmei; Ren, Lishun; Ding, Yuanyuan; Hou, Shuting (Frontiers in Pharmacology, 2021)
Airway remodeling is a primary pathological feature of asthma. The current therapy for asthma mainly targets reducing inflammation but not particularly airway remodeling. Therefore, it is worthwhile to develop alternative and more effective therapies to attenuate remodeling. Gu-BenFang-Xiao Decoction (GBFXD) has been used to effectively and safely treat asthma for decades. In this study, GBFXD regulated airway inflammation, collagen deposition, and the molecules relevant to airway remodeling such as Vimentin, α-SMA, hydroxyproline, and E-cadherin in chronic remission asthma (CRA) murine model. Proteomic analysis indicated that the overlapping differentially expressed proteins (DEPs) (Model/Control and GBFXD/Model) were mainly collagens and laminins, which were extracellular matrix (ECM) proteins. In addition, the KEGG analysis showed that GBFXD could regulate pathways related to airway remodeling including ECM-receptor interactions, focal adhesion, and the PI3K/AKT signaling pathway, which were the top three significantly enriched pathways containing the most DEPs for both Model/Control and GBFXD/Model. Further validation research showed that GBFXD regulated reticulon-4 (RTN4) and suppressed the activation of the PI3K/AKT pathway to alleviate ECM proteins deposition. In conclusion, our findings indicate that GBFXD regulate the PI3K/AKT pathway via RTN4 to improve airway remodeling, which provides a new insight into the molecular mechanism of GBFXD for the treatment of CRA.